Regulation of ompC and ompF expression in Escherichia coli in the absence of envZ. - Forst, S (1988)
The expression of the genes encoding the major outer membrane porin proteins OmpF and OmpC in Escherichia coli is regulated by ompR, which encodes the transcriptional activator protein OmpR, and envZ, which encodes a receptorlike protein located in the inner membrane. To examine the role of EnvZ in the expression of the osmoregulated porin genes, we analyzed the production of OmpF and OmpC in cells that lack envZ function. We show that EnvZ is required for the maximal production of OmpC in cells grown in minimal medium but is not essential for the efficient induction of OmpC that occurs during a shift to a high-osmolarity medium. In contrast, the production of OmpF in cells that lack envZ function was similar to that of the parent strain, whereas OmpF repression during a shift to a high-osmolarity medium was incomplete in the absence of EnvZ. These results are discussed in the context of the putative role of EnvZ in the expression of ompF and ompC.